Production Process Improvement Design to Eliminate Waste in 428H Chain Products Using Lean Manufacturing at PT ABC - Sekar Aulia Putri; Amal Witonohadi; Annisa Dewi Akbari (OPSI, 2022)
PT ABC is a manufacturing company that produces several types of chains in large quantities, and one type of chain that is the main focus of this research is the 428H chain. The obstacle faced in producing the 428H Chain is not achieving the production target from June to July, and September to November 2021. The research focuses on minimizing manufacturing lead time using lean manufacturing by eliminating waste in the 428H Chain production process. Waste elimination is done by providing suggestions for improvements based on the identified waste types. The study begins with the calculation of the time sample, then MLT, PCE, the use of the Waste Assessment Model, and mapping current value stream mapping. The initial MLT was 832.95 minutes and PCE was 63.37%. WAM produces the highest percentage of waste in the type of defect, then motion, inventory, waiting, overproduction, motion, and process. The proposed improvements are in the form of designing SOP Operators on Pressing machines, adding Small Incline Belt Conveyor tools, designing SOPs for Activities in the WIP Area, and adding Manual Hand Stacker tools. The provision of improvement proposals resulted in MLT decreasing 12% to 733.2174 minutes and PCE increasing 8.6% to 71.98%, and the production target was achieved with total production per month increasing by 12%, from 21,783 to 24,746 units per month.